Pewarisan Budaya Ritual Pengantin Kecik Ka’aik Nari Di Masyarakat Suku Serawai Bengkulu Selatan - Cendrawani, Cendrawani; Sari, Sapta; Risdiyanto, Bayu (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The Kecik Ka'aik Nari Bride Ritual Ceremony is an indigenous culture of the Serawai tribe of South Bengkulu Regency. The Serawai tribe is an indigenous people in Bengkulu Province who perform the Kecik Ka'aik Nari bridal ritual ceremony on girls who are starting to enter adolescence or baligh, within the age range of 6-12 years. The child who is Ka'aik Nari undergoes several traditional rituals including ke Aik and Nari so that it is called Ka'aik Nari. This study aims to determine the process of inheriting the cultural tradition of the Kecik Ka'aik Nari bridal ritual to the younger generation of the Serawai tribe in Lubuk Ladung Village, South Bengkulu Regency. The type of research used is descriptive qualitative. The data collection techniques used are observation, interviews, documentation, and literature study. Based on the results of the research found in the cultural inheritance of the Kecik Ka`aik Nari bridal ritual in the Serawai Tribe Community of South Bengkulu, the process of inheriting the Kecik Ka`aik Nari bridal ritual to the younger generation in Lubuk Ladung village is carried out by involving the community and the younger generation starting from 6 years old, especially the female gender, the inheritance of the Kecik Ka`aik Nari bridal ritual culture from the traditional leader, village head, ritual leader to the younger generation by providing an understanding of the meaning, norms, and customary values that exist in each stage of the Kecik Ka`aik Nari bridal ritual process to the younger generation and about the importance of maintaining this tradition. This can be seen in every activity of the Kecik Ka`aik Nari bridal ritual event which always involves the community and the younger generation both to help the process of activities and enliven the Kecik Ka`aik Nari bridal ritual event.